Kemampuan Dribbling Bola Basket: Peran Koordinasi dan Percaya Diri - Syamsul Darmawan; Rachmat Hidayat; Andy Amry Yahya (Jurnal Porkes, 2026)
The basketball dribbling skills of students at SMAN 1 Soppeng are still not optimal. Some students often lose control of the ball when moving quickly or under pressure from opponents. In addition, their hand-eye coordination appears to be underdeveloped, and their confidence levels remain low. This study aims to determine the effect of hand-eye coordination and self-confidence on dribbling skills, both partially and simultaneously. The research method used a quantitative correlational-regressive approach with a sample of 30 male students participating in the SMAN 1 Soppeng basketball extracurricular program, selected through total sampling. Research instruments included a zig-zag dribbling test, a tennis ball throw-and-catch test, and a Likert-scale self-confidence questionnaire. Data analysis utilized descriptive statistics, classical assumption tests (normality, linearity, multicollinearity, heteroscedasticity), as well as simple and multiple linear regression. The results showed that hand-eye coordination had a significant effect on dribbling (R = 0.850; p < 0.001). Self-confidence also had a significant effect (R = 0.857; p < 0.001). Simultaneously, both variables had a significant effect with R = 0.901 and Adjusted R-Square = 0.797, meaning that 79.7% of the variation in dribbling ability is explained by these two variables. Conclusion: Eye-hand coordination and self-confidence jointly influence dribbling ability.